Co-generation of hydrogen and carbon aerosol from coalbed methane surrogate using rotating gliding arc plasma. (1st June 2017) - Wu, Angjian; Li, Xiaodong; Yan, Jianhua; Yang, Jian; Du, Changming; Zhu, Fengsen; Qian, Jinyuan
Highlights: Rotating gliding arc (RGA) is proposed in coal bed methane (CBM) conversion. The performance of CBM surrogate conversion in RGA is comprehensively evaluated. 2D graphene sheets are formed in CBM surrogate conversion by RGA discharge. Abstract: A novel atmospheric pressure non-thermal plasma, i.e., rotating gliding arc (RGA), is developed to upgrade coal bed methane (CBM) into hydrogen and carbon aerosol simultaneously. CH4 is used as a CBM surrogate. In present work, the V-I characteristics of RGA discharge in CH4 conversion are monitored with different gases (N2, Ar and CO2 ) as carrier gas, while the active species (such as OH, CH, CN, C2, excited molecules and ions) involved in the plasma reactions are identified by optical emission spectroscopy (OES). According to the sensitivity analysis of specific energy density (SED), the importance of operating conditions on SED sensitivity is in a sequence of CH4 concentration > applied voltage > residence time. The performance of CH4 conversions are comparatively evaluated based on the variation of operating conditions. In general, the enhancement of applied voltage and residence time effectively increases the CH4 conversions, selectivity of hydrogen, as well as the energy efficiency, while the augment of CH4 concentration has a negative effect in contrast. The carbon aerosol obtained in CH4 /N2 and CH4 /Ar discharge are comparatively investigated. Transparent crumped-like graphene sheets and spherical nanostructure carbon are observed in both obtained carbon aerosol, with relative high ID /IG ratios (∼0.62) indicated in Raman spectroscopy. High C/O ratios (>14) are obtained in the XPS survey spectra, with the intensity ratios of sp 2 CC/sp 3 C-C occupy about 80%. However, the BET surface area of carbon obtained from CH4 /N2 is almost 3 times larger than that from CH4 /Ar discharge. In addition, super hydrophobic and oleophilic properties are observed in both carbon samples. The contact angles of water droplets are above 130°, while the contact angle of oil is less than 4°.